ENGLISH SONGS AS MEDIA TO TEACH ENGLISH - Triayulin, Evy Nur (Jurnal Bahasa Lingua Scientia, 2012)
There were various kinds of media and methods available that can be used in teaching English. One kind of them is song. Song is not only a media of entertainment, but also could be used to learn the language. By using song, we could practice our skills, especially in listening and speaking. The song is a source of learning English through the spelling, writing, listening, pronouncing, and reading comprehension. Based on these views, the researcher is interested to conduct the research on the use of the foreign song as media to teach English to the 8th grade students at MTS Al-Huda Bandung. The formulation of the research problems were; how is foreign song used as media to teach English and what are the advantages on using foreign song as media in teaching English. The purposes of this research were to; describe how to use the foreign song as media to teach English, and describe the advantages on the use of foreign song as media in the teaching-learning process.